Editorial on Special Issue "Pharmaceutical Formulations with Antimicrobial Properties" - Anca N. Cadinoiu; Marcel Popa (MDPI AG, 2022)
Even though numerous studies on the systemic administration of antimicrobial drugs can be found in the literature, they still have many shortcomings related to the site-specific drug delivery, unwanted side effects and even potential toxicity [...]